The factors impacting on Gleason score upgrading in prostate cancer with initial low Gleason scores - Tzu-Heng Huang; Wei-Ming Li; Hung-Lung Ke; Ching-Chia Li; Wen-Jeng Wu; Hsin-Chih Yeh; Yen-Chun Wang; Hsiang-Ying Lee (Journal of the Formosan Medical Association)
Background: This study aims to investigate the factors contributing to the discrepancy in between biopsy Gleason score (GS) and radical prostatectomy GS in patients diagnosed with prostate cancer. Methods: 341 patients who underwent radical prostatectomy from 2011/04 to 2020/12 were identified. 102 Patients with initial GS of six after biopsy were enrolled. Preoperative clinical variables and pathological variables were also obtained and assessed. The optimal cut-off points for significant continuous variables were identified by the area under the receiver operating characteristic curve. Results: Upgrading was observed in 63 patients and non-upgrading in 39 patients. In the multiple variables assessed, smaller prostate volume (PV) (p value = 0.0007), prostate specific antigen density (PSAD) (p value = 0.0055), positive surgical margins (p value = 0.0062) and pathological perineural invasion (p value = 0.0038) were significant predictors of GS upgrading. To further explore preclinical variables, a cut-off value for PV (≤ 38 ml, p value = 0.0017) and PSAD (≥ 0.26 ng/ml2, p value = 0.0013) were identified to be associated with GS upgrading. Conclusion: Smaller PV and elevated PSAD are associated with increased risk of GS upgrading, whereas lead-time bias is not. A cut-off value of PV < 38 ml and PSAD > 0.26 ng/ml2 were further identified to be associated with pathological GS upgrading.